Analysis of the nystagmus characteristics of cupula diseases: A case report. Issue 1 (7th January 2022) - Wang, Zhaoxia; Zhang, Yang; Guo, Qiang; Lin, Ying; Li, Juan-Juan
Abstract: Introduction: Clinically, there is a kind of patients with positional vertigo or dizziness, which occurs when they turn left or right, look down or up, lie down or sit up. With a long duration and varying frequency, it is not consistent with the manifestations of benign paroxysmal positional vertigo (BPPV). In addition, the persistent geotropic direction-changing positional nystagmus (PG-DCPN) was observed in a supine head-roll test. Patient concerns: With no apparent trigger for visual rotation and a sense of self instability, an 81-year-old female patient had suffered from vertigo for 3 days. The vertigo occurred every day, lasting several minutes each time, and associated with head movements and changes in body position. In a supine head-roll test, it appeared persistent geotropic direction-changing positional nystagmus for a long time, without latency, fatigability and in the presence of 3 zero planes. Diagnosis: Light cupula. Interventions: Difenidol hydrochloride 25 mg orally 3 times/day for 2 weeks and betahistine hydrochloride 12 mg orally 3 times/day for 1 month were administered. Outcomes: After 1 month of treatment, the patient's vertigo symptoms disappeared. And in the supine head-roll test, the persistent geotropic direction-changing positional nystagmus disappeared. Conclusion: We report the characteristics of nystagmus produced in a typical patient with light cupula during the supine head-roll test. After reviewing the relevant literatures, we believe that a simpler method can be used to identify canalolithiasis and cupula disease, to distinguish light and heavy cupula, and to determine the pathological semicircular canal to which the lesion belongs.